Effects of psoralen on the pharmacokinetics of anastrozole in rats - Yuzhu Zhang; Jingjing Wu; Yue Zhou; Yulian Yin; Hongfeng Chen (Pharmaceutical Biology, 2018)
Context: Psoralen and anastrozole are always used together for breast cancer patients in Chinese clinics. Objective: This study investigates the effects of psoralen on the pharmacokinetics of anastrozole in rats and its potential mechanism. Materials and methods: The pharmacokinetics of orally administered anastrozole (0.5 mg/kg) with (test group) or without (Control group) psoralen pretreatment (20 mg/kg/day for 10 days) in male Sprague-Dawley rats (six rats in each group) were investigated. The plasma concentration of anastrozole was determined using a sensitive and reliable LC-MS/MS method. Additionally, the effects of psoralen on the intestine transport and metabolic stability of anastrozole (1 μM) were investigated using a Caco-2 cell transwell model and rat liver microsome incubation systems. Results: The results indicated that psoralen could significantly increase the Cmax (from 56.74 ± 3.17 ng/mL to 83.26 ± 6.87 ng/mL), and t1/2 (from 10.80 ± 1.05 to 14.29 ± 1.38 h) of anastrozole (p < 0.05). Psoralen could also significantly decrease the efflux ratio of anastrozole from 1.88 to 1.32 (p < 0.05). Additionally, the intrinsic clearance rates of anastrozole decreased significantly (from 62.83 to 43.97 μL/min/mg protein) (p < 0.05) with psoralen pretreatment in rat liver microsome incubation systems. Discussion and conclusions: This study indicates that when the rats were pretreated with psoralen, the system exposure of anastrozole would be increased significantly. The results showed that the herb-drug interaction between psoralen and anastrozole might occur when they were co-administered, and future studies in humans also need to investigate its herb-drug interaction potential.